Case report: Challenging kidney transplantation in an adolescent patient with tetralogy of Fallot - Jakšić, Ante; Barbalić, Berislav; Orlić, Lidija; Župan, Željko; Vujičić, Božidar; Gršković, Antun; Ćelić, Tanja; Chinchella, Ivana Koraca; Čače, Neven; Flajšman-Raspor, Sanja; Bubić, Ivan; Španjol, Josip; et al. (Frontiers in Medicine, 2024)
Tetralogy of Fallot is the most common cyanotic congenital heart disease. This severe disorder of cardiac physiology can impair renal function and lead to the development of cardiorenal syndrome and eventually to end-stage renal disease. Kidney transplantation may be the best option for renal replacement treatment in patients with tetralogy of Fallot, but only after correcting cardiac abnormalities and optimizing cardiac functions, all of which require a multidisciplinary approach. We report the first case of kidney transplantation in an adolescent patient with tetralogy of Fallot. Our findings confirms that kidney transplantation is a valuable treatment option in selected congenital heart disease cases.